The future dental workforce in Malaysia: drivers for change - Che Musa, Muhd Firdaus; Gallagher, Jennifer E.; Bernabe, Eduardo (2015)
Objective: To explore key stakeholders views on recruitment, retention, training and team working of the dental workforce in Malaysia and drivers for change. Methods: Elite players from key dental organisations and professions in Malaysia were invited to participate in an audio-taped semi-structured interview. The one-to-one interviews were conducted in English, which is the medium for dental education nationally, and used a pre-tested topic guide to test a framework influenced by the health workforce literature and previous research amongst Malaysian dental students. The qualitative data were transcribed and analysed using a Framework Analysis. Results: Elites from top level management representing government and non-government dental organisations; and representatives from dentistry and dental therapy agreed to participate (n=20). Thematic analysis suggests the main drivers influencing the future dental workforce in Malaysia include policy (growth in dental education; moratorium on dental schools) and politics (healthcare governance; trade liberalisation), social (neo-liberalisation including globalisation of dental education; value in academic success), economic (country wealth), demography (growing and ageing population, inequalities in oral health) and disease (caries levels, chronic diseases) as well as developments in science and technology (dental implants; cosmetic dentistry). The pace of change and possible interplay between drivers was a source of concern. Conclusion: Stakeholders’ views on drivers for change broadly mirror other studies in high income countries; however, specific challenges for Malaysia relate to the rapid expansion of dental education and a young workforce with significant aspirations. A broad and flexible strategy is required to overcome an issue of training and retention of the dental workforce; and the influence of globalisation for the benefit of healthcare systems and the population.